Leadership and governance frameworks driving transformational change in an entrepreneurial UK university. Issue 5 (8th July 2019) - Purcell, Wendy Maria; Chahine, Teresa
Abstract : Purpose: Disruptive megatrends, such as technology and globalization, are driving transformational change in universities as they seek to differentiate themselves given economic and social market forces. However, higher education (HE) institutions can struggle to achieve change at the scale and speed needed, given their pluralistic nature and competing goals. As primarily collegiate organizations run by academics, leadership and governance are by persuasion and consensus over diktat. A retrospective analysis of the transformational journey of a UK university that set its radical new mission to become "the Enterprise University" has been undertaken, and a new leadership and governance framework articulated. The paper aims to discuss this issue. Design/methodology/approach: Drawing upon a conceptual framework of leadership and governance to codify change management and its acceleration, the change journey in a university undergoing a strategic transformation has been analyzed. Leadership and organizational frameworks are examined focusing on the interactions between the senior management hierarchy (SMH), as the command-control operating system, and the adaptive community of social networks within the university and external stakeholders. The critical steps in effecting institutional change and the nature of the social agreements underpinning transformation are subject to retrospective analysis. How ideas flowed through the organization to create value through innovation is reviewed. Findings: Analyses reveal how the SMH worked with the adaptive social networks of staff and stakeholders in concert around a shared purpose, identifying enablers and barriers to a healthy idea flow. Drawing on the leadership and governance framework empowers organizational transformation, paying more deliberate attention to the stewardship of ideas and how change actually happens. To thrive in volatile, uncertain, complex and ambiguous environments and sustain competitive advantage in a dynamic global market place, leaders need to be able to harness the social forces and inspire people to take actions around a shared vision of the future. Originality/value: Universities represent a traditional community of knowledge workers and service professionals where approaches to leadership and governance are typically collegiate and consensual. Examining the strategic transformation of a university seeking to move at pace to accommodate the global disruption of the HE sector is relevant to how change happens in related environments. Given the growth of the knowledge economy, represented as organizations and networks, key lessons are available. The importance of activating people around shared purpose through deliberate engagement by leaders with social networks is relevant to delivering transformation in conditions of super complexity.